2004
DOI: 10.1097/01.tp.0000107287.70512.e7
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous black fungus (phaeohyphomycosis) infection in renal transplant recipients:three cases

Abstract: We describe three cases of subcutaneous phaeohyphomycosis developing in the lower limbs of renal transplant recipients shortly after transplantation. Each case presented with dark-colored nodules that subsequently ulcerated. Histopathologic examination revealed dematiaceous fungal hyphae with a surrounding granulomatous reaction. The fungi were subsequently identified as Alternaria alternatum in two cases and Phialophora richardsiae in one case. In one case, the lesions resolved during a prolonged (6-month) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 11 publications
(12 reference statements)
0
40
0
5
Order By: Relevance
“…6,48 At our institution all patients received surgical treatment for phaeohyphomycosis and 11 (64.7%) of 17 patients also received systemic antifungal therapy with itraconazole. Although amphotericin B, 16,35,49 fluconazole, 50 ketoconazole, 49,51 and 5-fluorocytosine 21,49 have been proposed for the treatment of phaeohyphomycosis, these drugs were considered as alternative therapy for those patients with severe disease, poor response, or hepatic toxicity to itraconazole.…”
Section: Discussionmentioning
confidence: 99%
“…6,48 At our institution all patients received surgical treatment for phaeohyphomycosis and 11 (64.7%) of 17 patients also received systemic antifungal therapy with itraconazole. Although amphotericin B, 16,35,49 fluconazole, 50 ketoconazole, 49,51 and 5-fluorocytosine 21,49 have been proposed for the treatment of phaeohyphomycosis, these drugs were considered as alternative therapy for those patients with severe disease, poor response, or hepatic toxicity to itraconazole.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients are immunocompetent, and they often are from a rural background, i.e., farmers with frequent, minor trauma from plant material or gardeners (133,192,206,233,277,359,576,751,815). Organ transplantation is also a common risk factor (28,38,112,142,235,236,262,271,286,296,465,484,514,556,587,645,679,704,725).…”
Section: Phaeohyphomycosismentioning
confidence: 99%
“…Clinically significant species in the mostly wood-inhabiting genus Pleurostomophora include P. richardsiae (obsolete Phialophora richardsiae) and P. repens (obsolete Phialophora repens), and individuals acquiring these mycoses are commonly immunocompromised (369,601,815). Species are anamorphs of the genus Pleurostoma.…”
Section: Sordarialesmentioning
confidence: 99%
“…Maha Yahin et al, reported three cases of subcutaneous skin infection with pheohyphomycosis of lower extremities in RT recipients [10].…”
Section: Discussionmentioning
confidence: 99%